GROWTH AND DEVELOPMENT OF LITERARY SOCIETIES BETWEEN 1911- 1967 IN PUDUCHERRY - Dhaivamsam, N. (International Journal of Psychosocial Rehabilitation, 2020)
The culture of Puducherry was influenced by various rulers from time to time. Literature survey revealed that Puducherry facilitated the transition and transformation of Puducherry culture by thirteen literary societies. These literary societies are Alliance Francaise, Ecole Francaised’ Extreme orient, Institute francais, Historical Society of Pondicherry, Societe Progressiste , KalaimaghalKazhagam Pondicherry, Tamil Talir Kazhagam, Alliance educative des vannias Pondicherry, Kalvikahazhagam Pondicherry, Puthuvai Tamizh Sangam, Karai Kalvi Kazhagam, Siddha Vaidya Sangam, Pondicherry State Sangeetha Nataka Sangam. The influence of these literary societies on the culture of Puducherry is studied in this research paper. It is understood that these literary societies acted as buffer resisting sudden change in the culture and facilitating harmonization of the Indian and French culture. Further these societies generalized and popularized the fittest culture points and practices.